Tinjauan Terhadap Pengalaman dan Jumlah Tanggungan Keluarga Petani pada Petani Karet Menghasilkan di Desa Jangkang Benua Kabupaten Sanggau - Youlla, Donna; Widarti, Sri; Herlin, Kristin (Prodi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Panca Bhakti, 2024)
Rubber is one of the plantations with high economic value, rubber is also one of the plantations that is widely cultivated as a source of income. Rubber plantations are one of the livelihoods of the majority of the people of Tanggang Benua Village, Tanggang District. Rubber commodities in Jangkang District have quite large production, but their income does not match the production they get. This research aims to determine the farming experience and the number of dependents of families of rubber farmers who produce rubber in the village ofJangng Benua. This research was conducted in Jangjang Benua Village, Jangjang District, Sanggau Regency. This location was determined deliberately with the consideration that Jangkang Benua Village is one of the villages with quite large rubber production in Jangkang District. Data collection in this research was carried out using a survey method. The data used are primary and secondary data. The data that has been obtained is then analyzed using qualitative descriptive analysis and quantitative descriptive analysis. The sample used in this research was 32 rubber farmers. 3 (three) variables are components in reviewing farmers' farming experience, the responsibilities of the farmer's family and the income received by rubber farmers. The longest farming experience undertaken by farmers is 18 - 28 years with an average income of Rp. 3,948,000, smaller than those with less experience. The maximum number of dependents in a farming family is 7 people and the income received is also the largest. From this research, it can be seen that the average production of rubber farmers in Jangkang Benua Village is 570 kg. While the selling price is IDR 7,000, the average income obtained by farmers is IDR 3,990,000.